The Role of Governor as Vice of Central Government in Regional Regulatory Oversight Regional Tax & Regional Retribution - Muhammad Rois (Universitas Islam Sultan Agung, 2021)
This study aims to discuss and analyze the role of the Governor as the Representative of the Central Government in the supervision of Regional Regulations on Regional Taxes and Levies in accordance with Act No. 23 of 2014 concerning Regional Government. The research method uses normative juridical. The results show that the mechanism carried out by the Governor as the Representative of the Central Government is the supervision of Regency Regional Regulations concerning Regional Taxes and Regional Retributions according to Act No. 23 of 2014 which prioritizes the evaluation aspects of the draft District/City Regional Regulations concerning Regional Taxes and Regional Levies before obtaining approval .